The Relationship Between Employment Status and Prior Education to Academic and Clinical Success for Diagnostic Medical Sonography or Radiography Students. - Miller, Elena (Journal of Diagnostic Medical Sonography, 2024)
Objective: It has been reported that employment during student enrollment, in rigorous health care programs, impedes college success and may be a barrier to successful graduation. Furthermore, student's prior education is typically viewed as a positive predictor of success in college. The aim of this study was to examine whether a relationship exists between employment status and prior education, compared with academic and clinical success for Diagnostic Medical Sonography (DMS) or Radiography (RT) students, in a large community college. Materials and Methods: There were 26 imaging student participants consented to this study. This convenient sample included 10 DMS and 16 RT students, enrolled in an associate degree in applied sciences program. A survey was administered that collected demographic data on the students in both programs. Data collection began at the start of each respective program and again one year later. Student academic and clinical grades were examined over a period of three college semesters. Results: The analysis of the findings did not show a significant relationship between employment status, prior education, student academics, and clinical success among the participating DMS or RT students. Conclusion: The results of this study provide limited evidence that there was no significant relationship between employment status, prior education, and academic and clinical success among this cohort of DMS or RT students. These findings also suggest that students' employment did not impede success for these DMS and RT students. In addition, this research shows that students' prior education had no effect on their success in their DMS and RT programs. Further research should be conducted to investigate whether these findings are similar in other imaging programs.